ACTIVITY BASED COSTING APPROACH TO FINANCIAL MANAGEMENT IN THE PUBLIC SECTOR: THE SOUTH AFRICA EXPERIENCE - Emmanuel Kojo Oseifuah (European Scientific Journal, ESJ, 2013)
After 1994, the newly elected democratic government of South Africa radically reformed its public sector. One of the most important reforms is the introduction of the Public Finance Management Act 1999 (PMFA) aimed at improving financial management in the public sector. The study investigates the impact and possible concomitant improvement in financial performance consequent upon the use of activity based costing (ABC) and the conditions under which such improvement is achievable in the South African public sector. The case study method was employed to collect and analyse data relating to improvement in financial performance, perception and success of ABC in the Buffalo City Municipality in the Eastern Cape Province of South Africa. The study reveals that ABC provides significantly more accurate and useful information than traditional cost accounting. The results indicated further that management strongly agree that ABC utilisation improves insight into causes of cost; provides better cost control and cost management; provide better understanding of cost reduction opportunities; improves managerial decision making; and provides more accurate information for product or service costing and pricing. Management also agrees that ABC use improves financial performance. The study is significant because it highlights the important role that ABC plays in improving financial management in the public sector. ABC use can be recommended for public sector organisations to provide decision makers (e.g. legislators, public officials and administrators) with valuable information and cost data. The cost data can be significant because they will give decision makers the opportunity to make optimal choices about how to allocate limited resources. Finally, ABC data will enable decision makers to streamline and restructure public entity operations and processes to ensure effectiveness and efficiency.